Perwujudan Sikap Zuhud dalam Kehidupan - Tri Wahyu Hidayati (Institut Agama Islam Negeri (IAIN) Salatiga, 2016)
There are some people give negative assumptions of zuhud. According to them, zuhud is an attitude avoiding world, wealth and position. Hence, based on their assumption, zahid is a person who is shabby, even seedy. Is that the meaning of zuhud? Therefore, this paper is present to critisize the zuhud understanding, the characteristics of persons being zuhud, the factors which influence or cause them become zuhud, and the impacts of zuhud attitude in human life. This paper is important to give the new paradigm of the concept of asceticism and its application in modern life, especially the Indonesian nation is experiencing a multidimensional crisis. This paper is descriptive exploratory study to get the information of the definition, characteristics, causes and effects of being zuhud. The data were obtained from interviews with four lecturers at IAIN Salatiga. The result of this study would be analyzed with the theoretical framework of the Qur'an verses and hadith, and combined with the concept of zuhud based on of the Sufis.